Effects of Ethanol and Ethyl Acetate Extracts of Garlic (Allium sativum) on the Growth of Escherichia coli Extended Spectrum β-Lactamase - Ulya, Rohmatul; Arfiyanti, Mega Pandu; Rakhmawatie, Maya Dian (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: The prevalence of Extended Spectrum β-Lactamase (ESβL) Escherichia coli has increased by 0.91 – 2.31% per year and causes β-lactam antibiotics to be useless. Natural medicines such as garlic can be used to treat antibiotic resistance. It has been reported that garlic ethanol extract can inhibit the growth of Metallo-β-lactamase E. coli, but there have been no reports of garlic ethyl acetate extract activity against resistant bacteria. Objective: This study aims to prove the effect of ethanol and ethyl acetate extracts of garlic in inhibiting the growth of ESβL E. coli. Methods: The ethanol and ethyl acetate extracts of garlic were prepared in concentrations of 25, 50, 75 and 100% w/v, and were tested on ESβL E. coli using the disc diffusion assay. This study used a post-test-only control group design with meropenem as the positive control. The effectiveness of both garlic extracts was assessed from the inhibition zones formed around the discs. Phytochemical tests were carried out to see the compound content of garlic extract. Results: All concentrations of garlic ethanol extract were not significantly different in inhibiting ESβL E. coli growth (with inhibition zone diameter 2.82 - 3.30 mm). However, for the ethyl acetate extract, the higher the concentration the higher the activity of the extract in inhibiting ESβL E. coli (p-value <0.05). The best inhibition zone of ethyl acetate extract was 4.18 mm at a concentration of 100%. Meropenem as a positive control produced a 17 mm inhibition zone. The ethanol and ethyl acetate extracts of garlic had no difference in the active compound content, both contain tannins, saponins, and essential oils. Conclusion: The ethanol and ethyl acetate extract of garlic had weak potential to inhibit ESβL E. coli growth when compared to meropenem as a control drug.